Kesesuaian Penyelesaian Pembiayaan Bermasalah pada Akad Murabahah dengan Fatwa DSN-MUI Nomor 47 dan 48 Tahun 2005: (Studi di KSPPS Bmt Huwaiza Depok) - Aisyah Shofiyah Karimah; Ahmad Hanif; Addys Aldizar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze the implementation of problematic murabahah financing settlement at KSPPS BMT Huwaiza Depok and assess its compliance with the DSN-MUI Fatwa Number 47 and 48 of 2005. The approach used is descriptive qualitative with the type of normative-empirical Islamic law research. Data were obtained through interviews, observations, and documentation, which were then analyzed descriptively comparatively between field practices and the provisions of the fatwa. The results of the study indicate that the settlement of problematic financing is carried out in stages, starting with a persuasive approach, issuing warning letters, to restructuring through rescheduling and collateral sales. The rescheduling practice is carried out without increasing the amount of debt, only adjusting the payment period, while collateral sales are carried out based on market prices with the principle of justice. In conclusion, the implementation of problematic murabahah financing settlement at KSPPS BMT Huwaiza is in accordance with sharia principles and the DSN-MUI Fatwa, although the sharia arbitration mechanism has not been implemented.